2015
DOI: 10.1007/s11523-015-0379-4
|View full text |Cite
|
Sign up to set email alerts
|

HPMA Copolymer-Conjugated Pirarubicin in Multimodal Treatment of a Patient with Stage IV Prostate Cancer and Extensive Lung and Bone Metastases

Abstract: Nanomedicine allows achievement of tumor-selective drug delivery because of the enhanced permeability and retention (EPR) effect of solid tumors. We report here the first clinical application of a new agent-HPMA copolymer-conjugated pirarubicin (P-THP)-with a molecular size of about 8 nm, or 38.5 kDa. A patient had advanced prostate cancer with multiple metastases in the lung, pelvis, femur, and perhaps the sacrum. In April 2013, this 60-year-old patient started treatment with leuprorelin and estradiol, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…In this case, the activity of cathepsin B is not essential for biological activity of the conjugate. One such conjugate consisting of hydrazone linker and drug pirarubicin (P-THP) has been applied together with proton beam radiation to a patient with stage IV prostate cancer and extensive metastases, resulting in complete remission and no evidence of relapse was observed after 20 months [36]. …”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
“…In this case, the activity of cathepsin B is not essential for biological activity of the conjugate. One such conjugate consisting of hydrazone linker and drug pirarubicin (P-THP) has been applied together with proton beam radiation to a patient with stage IV prostate cancer and extensive metastases, resulting in complete remission and no evidence of relapse was observed after 20 months [36]. …”
Section: The Development Of the Second Generation Of Hpma Copolymementioning
confidence: 99%
“…Other polymer such as HPMA [N-(2-hydroxypropyl)methacrylamide] conjugated to pirarubicin via hydrazone bonds showed high therapeutic potential against lung cancers [109]. This conjugate was found to improve the treatment of metastases in patient suffering from stage IV lung cancer.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Polymeric micelles constructed from polymeric prodrug of hydrophobic small molecular drugs have emerged as a very promising choice considering its good water solubility, easy to further modification, enhanced permeability and retention (EPR) effect, and tunable drug content. [18][19][20][21][22][23][24][25][26][27] Moreover, it was reported that the introduction of tumor-targeting moieties onto polymeric prodrugs can effectively enhance the accumulation in tumor tissues and therapeutic efficacy of drugs. 28 In this context, somatostatin receptors (SSTRs) were explored as potential targets because they are overexpressed in a variety of tumors and cancer cell lines, including breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…36 It is worthy of noting that in addition to physically encapsulating drugs by nanoparticles, polymeric prodrug is another promising strategy owing to its intrinsic advantages such as passive targeting via the EPR effect, increased circulation time, improved water solubility, and tunable and well-defined drug content. [18][19][20][21][22][23][39][40][41][42][43][44] Besides, premature/burst drug release, which is one of the most common shortcomings of encapsulating method, can be effectively addressed. By using responsive chemical bonds to link drugs and polymers, polymeric prodrug can effectively release drugs under specific stimuli when reached into tumor tissues or cancer cells but released little drug in the circulation period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation